Analyzing Regional Legal Measures for Subsidizing Restrictions on Community Activities (PPKM) during the Covid-19 Pandemic: A Study of State Administrative Law in Java and Bali Regions - Arifianto, Rizky; Sjarif, Fitriani Ahlan (Nurani Hukum, 2023)
In recent years, Indonesia and the world have faced an unprecedented non-natural disaster, namely the Covid-19 Virus, which has severely impacted the economies of almost all countries. In response, Indonesia has implemented various legal instruments, including legislation and policy regulations, to address the crisis. One of the controversial legal instruments in Indonesia is the Minister of Home Affairs' Instruction Number 15 of 2021, which pertains to the enforcement of restrictions on community activities in Java and Bali due to the Covid-19 pandemic. This paper examines the implementation of this instruction by the regions of Java and Bali, focusing on the policy regulations issued in response. The research methodology employed in this study is normative juridical research (Legal Research). The findings reveal that policy regulations are distinct from legislation and that the regions, including DKI Jakarta Province, Banten Province, Central Java Province, West Java Province, East Java Province, and Bali Province, have issued various legal instruments to comply with the Minister of Home Affairs' instruction. However, both the central and regional governments must ensure that these legal instruments meet the requirements stipulated in the applicable laws and regulations. As Indonesia is a legal state, it is crucial for government officials to base their actions on the principles of the law.